2016
DOI: 10.1007/s10571-016-0440-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypoxia-Inducible Factor 1 in Mild Cognitive Impairment

Abstract: Neuroinflammation and reactive oxygen species are thought to mediate the pathogenesis of Alzheimer’s disease (AD), suggesting that mild cognitive impairment (MCI), a prodromal stage of AD, may be driven by similar insults. Several studies document that hypoxia-inducible factor 1 (HIF-1) is neuroprotective in the setting of neuronal insults, since this transcription factor drives the expression of critical genes that diminish neuronal cell death. HIF-1 facilitates glycolysis and glucose metabolism, thus helping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 100 publications
1
39
0
Order By: Relevance
“…The induction of hypoxiasignaling pathways (e.g., HIF-1 stabilization) has been proposed as a therapeutic target for mitigating or preventing neurodegenerative diseases such as cerebral ischemic stroke, Alzheimer's disease, Parkinson's disease, Huntington's disease, and prion-related diseases (59)(60)(61)(62)(63). HIF-1 triggers the expression of several genes involved in angiogenesis, oxygen transport, glycolytic metabolism, cell survival, apoptosis, and other processes that diminish neural cell death, increase cerebral blood flow, stimulate neurorepair process, and mitigate cognitive deterioration (59)(60)(61)(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of hypoxiasignaling pathways (e.g., HIF-1 stabilization) has been proposed as a therapeutic target for mitigating or preventing neurodegenerative diseases such as cerebral ischemic stroke, Alzheimer's disease, Parkinson's disease, Huntington's disease, and prion-related diseases (59)(60)(61)(62)(63). HIF-1 triggers the expression of several genes involved in angiogenesis, oxygen transport, glycolytic metabolism, cell survival, apoptosis, and other processes that diminish neural cell death, increase cerebral blood flow, stimulate neurorepair process, and mitigate cognitive deterioration (59)(60)(61)(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that HIF regulation has primarily been thought oxygen concentration, several studies have showed that HIF-1α can have an oxygen-independent regulation, such as in response to hyperglycemia, oxidative stress, and inflammatory proteins ( Cramer et al, 2003 ; Catrina, 2014 ; Corcoran and O’Neill, 2016 ). Hypoxia is an important factor in the pathophysiology of a number of human diseases (e.g., obesity, insulin resistance, diabetes, Alzheimer disease, and aging) that are characterized by the presence of inflammatory processes ( Eltzschig and Carmeliet, 2011 ; Iyalomhe et al, 2017 ). Hypoxia can also lead to the production of oxygen radicals, which, as well, have important implications in these diseases.…”
Section: Hif Canonical Pathway and Cellular Functionsmentioning
confidence: 99%
“…Increased HIF-1a expression and activity have been shown to promote glycolysis and glucose metabolism, thus countering oxidative stress by producing NADH and NADPH to propagate neuroprotective responses (Soucek et al 2003). HIF-1a has also been shown to improve cerebral blood flow, which could oppose the toxicity of hypoxia (Iyalomhe et al 2017). Overexpression of HIF-1a and/or HIF-1a target genes, such as VEGF-A and EPO, may be an early adaptation to the oxidative stressors that characterize MeHginduced neuropathology.…”
Section: Introductionmentioning
confidence: 99%